Dynamics of Suspended Cable Driven Parallel Robots Using the Geometric Variable Strain Approach - Mathew, Anup Teejo; Ben Hmida, Ikhlas; Mustafa, Suad Alhaj; Ahmed, Ahmed Nader; Al-Rub, Rashid K. Abu; El-Khasawneh, Bashar; Renda, Federico (IEEE International Conference on Soft Robotics (Online), 2023)
Construction 3D printing technology has recently received significant attention as a method for creating construction components or printing entire buildings. The deployment of Cable Driven Parallel Robots (CDPRs) in large-scale 3D printing is being explored as a potential candidate due to their low cost, high speed, and design modularity. However, the cable's inertial and elastic properties may lead to sagging and vibration, making the system difficult to model. In this paper, we use the Geometric Variable Strain (GVS) model, a geometrically exact approach based on the Cosserat rod theory, to model the dynamics of a CDPR. The Cosserat rod theory accounts for deformation modes that are not considered in other models, while the geometric formulation ensures accurate and fast computation. We compare the dynamic simulation of a small-scale CDPR prototype at different speeds and with an experimental setup. We also study the dynamics of a large-scale system subject to step loading. We show that analyses of CDPR systems using the GVS approach can reveal new perspectives on their control, design, and development.